Ecological and behavioral mechanisms of density‐dependent habitat expansion in a recovering African ungulate population. Issue 4 (23rd August 2021) - Becker, Justine A.; Hutchinson, Matthew C.; Potter, Arjun B.; Park, Shinkyu; Guyton, Jennifer A.; Abernathy, Kyler; Americo, Victor F.; da Conceiçāo, Anagledis; Kartzinel, Tyler R.; Kuziel, Luca; Leonard, Naomi E.; Lorenzi, Eli; et al.
Abstract: Major disturbances can temporarily remove factors that otherwise constrain population abundance and distribution. During such windows of relaxed top‐down and/or bottom‐up control, ungulate populations can grow rapidly, eventually leading to resource depletion and density‐dependent expansion into less‐preferred habitats. Although many studies have explored the demographic outcomes and ecological impacts of these processes, fewer have examined the individual‐level mechanisms by which they occur. We investigated these mechanisms in Gorongosa National Park, where the Mozambican Civil War devastated large‐mammal populations between 1977 and 1992. Gorongosa's recovery has been marked by proliferation of waterbuck ( Kobus ellipsiprymnus ), an historically marginal 200‐kg antelope species, which is now roughly 20‐fold more abundant than before the war. We show that after years of unrestricted population growth, waterbuck have depleted food availability in their historically preferred floodplain habitat and have increasingly expanded into historically avoided savanna habitat. This expansion was demographically skewed: mixed‐sex groups of prime‐age individuals remained more common in the floodplain, while bachelors, loners, and subadults populated the savanna. By coupling DNA metabarcoding and forage analysis, we show that waterbuck in these two habitats ate radically different diets, which were more digestible and protein‐rich in the floodplain than in savanna; thus, although individuals in both habitats achieved positive net energy balance, energetic performance was higher in the floodplain. Analysis of daily activity patterns from high‐resolution GPS‐telemetry, accelerometry, and animal‐borne video revealed that savanna waterbuck spent less time eating, perhaps to accommodate their tougher, lower‐quality diets. Waterbuck in savanna also had more ectoparasites than those in the floodplain. Thus, plasticity in foraging behavior and diet selection enabled savanna waterbuck to tolerate the costs of density‐dependent spillover, at least in the short term; however, the already poorer energetic performance of these individuals implies that savanna occupancy may become prohibitively costly as heterospecific competitors and predators continue to recover in Gorongosa. Our results suggest that behavior can provide a leading indicator of the onset of density‐dependent limitation and the likelihood of subsequent population decline, but that reliable inference hinges on understanding the mechanistic basis of observed behavioral shifts.